Relationship Between Knowledge About Personal Hygiene and Incidence of Urinary Tract Infections - Ransun, Djoni; Tuegeh, Johana; Tuwo, Lisa Stevany R.; Majuntu, Astrindo Maria (Jurnal Ilmiah Perawat Manado (Juiperdo), 2022)
Background: The number of UTI sufferers in Indonesia is 95 cases, 104 residents per year or around 180,000 new cases per year. One of the factors causing UTI is the lack of knowledge about personal hygiene, especially in the urogenital area. Purpose: This study aims to determine the relationship between personal hygiene knowledge and the incidence of UTI. Methods: Literature review, a comprehensive summary of several research studies based on themes. Literature search using PubMed and Google Scholar databases. The research design used a cross-sectional design, taken from articles published in 2015 to 2020. Results and analysis: the researchers found 5 articles that were feasible and met the inclusion criteria of the relationship between personal hygiene knowledge and the incidence of UTI. Discussion and conclusions: In this study, through these journals that have been identified and analyzed, it can be concluded that there is a relationship between personal hygiene knowledge and the incidence of urinary tract infections. Urinary tract infections can be experienced by children, adolescents, adults and the elderly, especially with various factors that can cause urinary tract infections such as gender, age, lack of drinking water, holding urine and so on. Keyword: Personal Hygiene, Urinary Tract Infection